2015
DOI: 10.1111/adj.12279
|View full text |Cite
|
Sign up to set email alerts
|

Dental demographics and metrics of oral diseases in the ageing Australian population

Abstract: One of the biggest challenges currently facing the dental profession in Australia is the provision of quality and timely dental care to the elderly. Adults aged 65+ years are an exponentially growing section of the community with rapidly changing dental needs, thanks in part to improvements in oral health over the past 60 years that have resulted in a dramatically decreased rate of edentulism and subsequently an increased number of teeth present. This is a challenge not only for the public dental services, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…They revealed that the more percent's of studied sample had tooth loss. This result also agrees with the results of the study by [27].Who studied "Dental demographics and metrics of oral disease in the aging Australian population". He found that the most of the studied sample had tooth loss.…”
Section: Discussionsupporting
confidence: 91%
“…They revealed that the more percent's of studied sample had tooth loss. This result also agrees with the results of the study by [27].Who studied "Dental demographics and metrics of oral disease in the aging Australian population". He found that the most of the studied sample had tooth loss.…”
Section: Discussionsupporting
confidence: 91%
“…The ageing of the world's population has led to the World Health Organisation's call for public health action and an international symposium for securing the oral health of older people . In Australia, it is estimated that by 2061 more than 22% of the population will be 65 years or older with some 10 to 20 per cent of the older population being frail, suggesting the need for a comprehensive professional understanding of the oral health needs of frail older people.…”
Section: Introductionmentioning
confidence: 99%
“…As such, this was considered as the current practice for the purposes of this study. Regrettably, evidence shows that poor oral hygiene is prevalent among RACFs’ residents . For this reason, and because many randomised controlled trials (RCTs) and systematic reviews (SRs) used the same current practice as the control group, it was assumed to have the baseline effectiveness value in the prevention of pneumonia cases (ie, 0%; Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Aged care residents have long been identified as a subpopulation at greater risk of developing oral diseases . This is due to a combination of factors such as obstacles to accessing proper oral health care services, polypharmacy and compromised medical health and cognitive and physical disabilities that affect the ability to maintain satisfactory oral hygiene, which leads to dependence on others to receive it . Increasing evidence associates poor oral health with a range of medical conditions, including aspiration pneumonia, bacteraemia, cardiovascular disease, atherosclerosis and stroke …”
Section: Introductionmentioning
confidence: 99%